Discount Rates in Risk v. Money and Money v. Money Tradeoffs - Anna Alberini; Aline Chiabai (Fondazione Eni Enrico Mattei (FEEM), 2006)
We use data from a survey of residents of five Italian cities conducted in late Spring 2004 to estimate the discount rates implicit in (a) money v. future risk reductions and (b) money v. money tradeoffs. We find that the mean personal discount rate is 2% in (a) and 8.7% in (b). The latter is lower than the discount rates estimated in comparable situations in many recent studies, greater than market interest rates in Italy at the time, and exhibits modest variation with age and gender. The discount rate implicit in money v. risk tradeoffs is in line with estimates from studies in the US and Europe, and does not depend on observable individual characteristics.
Keywords: J17; I18; D91; 330; Value of a statistical life; Latent risk reductions; Individual discount rates; Stated preference questions; Menschen; Bewertung; Abzinsung; Risiko; Italien; Wert des Lebens